Saliva diagnostics in patients suffering from bisphosphonate-associated osteonecrosis of the jaw: Results of an observational study. Issue 2 (February 2020) - Stockmann, Philipp; Ebker, Tobias; Bergauer, Jasmin; Wehrhan, Falk
Abstract: Objective: One of the severe side effects of bisphosphonate (BP) therapy is bisphosphonate-associated osteonecrosis of the jaw (BONJ). However, there is no information available about its pathogenesis. Hence, the aim of this observational study was to contribute to discerning this pathogenesis by comparing salivary quantity and quality in patients with BONJ and undergoing BP treatment. Materials and methods: This study included 60 patients divided into three groups. The first group consisted of 20 patients with established BONJ, the second group had 20 patients undergoing BP treatment, and the third group comprised 20 healthy individuals. These groups were analysed for the flow rate of stimulated saliva, buffer capacity, and salivary pH level. Results: Reduced salivation was observed in a significantly high number of patients with established BONJ ( n = 8) and those undergoing BP treatment ( n = 9) in comparison with the healthy control group ( n = 4; p = 0.039). Though the distribution of the mean value of stimulated saliva flow rates in patients undergoing BP treatment was lower than in the control group, the difference was not significant. Moreover, there were no significant differences in the salivary pH level and buffer capacity in patients undergoing BP treatment as compared with the healthy control group. Conclusions: It is possible that the quantity of human saliva is affected by BP treatment. This reduction in saliva production could have a negative effect on mucosal health and is perhaps a cofactor in the pathogenesis of BONJ.